Residual effect of compost, compost tea and inorganic fertilizer on growth, yield and nutrient composition of maize (Zea mays L). (2017)
The use of organic amendments has contributed immensely to crop yield and productivity due to their agronomic and environmental benefits. Among these benefits is the ability of organic amendments to stay longer in the soil unlike inorganic fertilizers. Greenhouse experiment was conducted to compare the residual effect of dry compost, compost tea and inorganic fertilizer on the growth, yield and nutrient uptake of maize (Zea mays L.) immediately after the first planting. The initial treatments consisted of dry compost (made from Mexican sunflower and poultry manure), compost tea (water extract from dry compost) and inorganic fertilizer (N.P.K 15:15: 15). Dry compost was applied at three levels (5, 10 and 15 t ha'), compost tea (200, 400 and 600m ha" and inorganic fertilizer at 100 and 150kg N ha". These were arranged in Completely Randomized Design (CRD) with four replicates. Data were collected on growth and yield parameters, pre and post-planting soil nutrient compositions as well as plant nutrient analysis. Results showed that compost application generally enhanced the growth and dry matter accumulation of maize in the residual trial compared to compost tea and inorganic fertilizer. However, compost had significant effects on the growth and yield of the maize compared to compost tea and inorganic fertilizer with the highest mean values recorded in maize crop treated with dry compost at 150/ha. This treatment increased the dry matter yield by 144% compared to control and inorganic fertilizer treatments. Plant tissue and post cropping soil nutrient analyses also revealed that application of organic amendments increased the residual concentration of phosphorus, potassium and calcium both in the soil and in the maize plant. Highest rate (600m'ha") of compost tea however increased growth and yield parameters compared to other rates in the residual trial. In conclusion, residual effect of compost is more pronounced on growth, yield and nutrient uptake of maize compared to compost tea and inorganic fertilizer.